Revealing social values in the context of peer-to-peer energy sharing: a methodological approach - Klein, Lurian Pires (2021)
Tese de Doutoramento em Sistemas Sustentáveis de Energia apresentada à à Faculdade de Ciências e Tecnologia da Universidade de Coimbra.